Nutrition-sensitive agri-food systems for resilient and sustainable Asian mega-deltas - Wismen, Ben (WorldFish, 2022)
Partners from Bangladesh, Cambodia, Vietnam and the Philippines attended the Asian Mega-Deltas (AMD) Initiative’s research planning and design workshop at WorldFish headquarters in Penang, Malaysia to develop holistic work plans to implement nutrition-sensitive approaches in policy and interventions to transform deltaic agri-food systems. Deltaic food systems are hit by serious impacts of climate change and climate extremes that will slow down economic growth, further erode food and nutrition security, exacerbate urbanization and migration challenges as well as trigger new poverty traps and emerging hotspots of hunger.